ICSID Sebagai Lembaga Arbitrase Penyelesaian Sengketa Penanaman Modal Asing Bagi Indonesia Dan Praktiknya - Ainunnisa Rezky Asokawati (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Foreign investment in Indonesia is one of the efforts to develop the country's economy. Foreign investment is carried out by doing business in Indonesia, which is to invest in the form of foreign capital entirely or collectively with domestic investors. This practice is carried out by foreign investors with the existence of international treaty between Indonesia and its country as legal protection when investors invest in Indonesia, which can also choose a dispute resolution forum as a preventive action agreed by both parties. Through the Washington Convention, Indonesia ratified Law Number 5 of 1968 which is a form of Indonesia's commitment to resolved at the International Centre for the Settlement of Investment Disputes or ICSID. ICSID is an international arbitration institution that can be chosen based on certain provisions. This research was conducted using normative juridical method. The results are found that ICSID becomes a forum when Indonesia is in dispute with foreign investors who are also countries that ratify the Washington Convention. The Government of Indonesia has several times defended its international standing on the investment climate in the country through the ICSID forum. Therefore, this paper will examine ICSID as an investment dispute settlement institution and its practices.